Comparative study on GMI properties of Co-based microwires improved by alcohol and liquid nitrogen medium-current annealing. (4th June 2021) - Liu, Rui; Cao, Guanyu; Liu, Jingshun; Li, Ze; Zhang, Yun; Liu, Zetian
Abstract: This work comparatively investigates the influence of alcohol and liquid nitrogen medium-current annealing on GMI effect of rotated-dipping Co-based microwires. The temperature field distribution of Co-based microwires during current-annealing process is accordingly simulated, further to acquire experimental parameters of annealing current. Experimental results indicate that, GMI characteristics of current-annealed microwires in mentioned two mediums are both significantly improved, and GMI ratio [Δ Z / Z max ]max and magnetic field response sensitivity ξ max of alcohol-medium current-annealed microwires increase more observable. When the excitation current frequency f  = 3 MHz, [Δ Z / Z max ]max and ξ max of microwires annealed by alcohol medium at 300 mA can reach 240.8% and 78.7%/Oe, respectively. During different type medium-current annealing, the higher-intensity annealing current can generate a larger circular magnetic field, which can effectively regulate the magnetic domain structure of Co-based microwires, so that, they tend to arrange densely and orderly, and the domain walls become much clearer. Meanwhile, the circular permeability μ φ of microwires is significantly improved, thereby enhancing their GMI characteristics. Accordingly, the medium-current annealed Co-based microwires can be used as a typically sensitive material to provide technical support for the potential application of micromagnetic measurement field.